Placing conditions on sharing general practice data for research: Recommendations from two community juries - Braunack-Mayer, Annette; Green, Heidi; Carolan, Lucy; Fabrianesi, Belinda; Adams, Carolyn; Flack, Felicity; Brown, Anthony; Miller, Kate; Hayter, Carrie; Rhee, Joel; Nettel-Aguirre, Alberto; Beilby, Justin; et al. (International Journal of Population Data Science, 2025)
Objective There is increasing demand for access to general practice health records for secondary purposes, including research. However, the extent to which the public supports such use is unclear. We sought to explore informed Australians' perspectives on conditions under which the use of general practice data for research would be acceptable. Methods We conducted two community juries in July and August 2023 with 20 participants, selected for diversity, in each jury. Jurors worked for 36 hours, in a combination of online and face-to-face sessions, over 6 days. They listened to expert presentations, discussed, and challenged experts, deliberated, and developed their own recommendations. Results Both juries, in principle, supported sharing general practice data for research purposes. They made 24 (Sydney jury) and 19 (Melbourne jury) recommendations related to consent, information provision, public benefit, data security, governance and costs. Conclusions The outcomes of the deliberative process suggest that an informed group of Australian citizens are willing to share general practice data for research provided strict conditions are met. Implications for Public Health Adopting the recommendations from the juries will require a range of policy and regulatory responses including legislative changes.